PENERAPAN MODEL PEMBELAJARAN SNOWBALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR DAN AKTIVITAS PESERTA DIDIK KELAS V SEKOLAH DASAR - Intika, Tiurida (Jurnal PGSD Musi, 2019)
The objective of research was to improve students' learning outcome on thematic learning through Snowball Throwing model in the fourth class of elementary school number 18 Palembang. The design of the research was action research. The subject of the research was 32 students of V including 14 male students and 18 female students. Technique of data analysis used test, observation and documentation. Based on the research result learning outcome, it was proved that the average score in cycle I increased first 66.87 with learning mastery 59.37% (enough), the average score in cycle I increased second 70.93 with learning mastery 68.75% (enough). The second cycle of the first meeting resulted in an increase in learning outcomes which was 84.37% with an average score of 86.25. The second cycle of the second meeting of learning outcomes increased to 87.50% with an average value of 89.37. The results of student learning activities in the first cycle of the first meeting were 66.67% (quite active), the second cycle of the second meeting was 75.26% (active), the second cycle of the first meeting was 80.98% (active), the second cycle of the second meeting increased to 86, 97% (very active). So, it can be concluded that using the Snowball Throwing model can improve student learning outcomes and activities.